Broadband Dual Circularly Polarized Magnetoelectric Dipole Antenna Fed by a Miniaturized Six-Branch Hybrid Coupler - Changhong Zhang; Xianling Liang; Junping Geng; Ronghong Jin (International Journal of Antennas and Propagation)
A broadband dual circularly polarized magnetoelectric dipole antenna (MEDA) fed by a miniaturized six-branch hybrid coupler (SBHC) is presented in this paper. First, a dual linearly polarized MEDA with a bandwidth of 73.3% is developed based on the previous design with a bandwidth of 52%. The SBHC, with a miniaturized size of 53%, is designed on a printed circuit board underneath the ground of the MEDA, which possesses an efficient bandwidth of 80.7% to generate the antenna for dual circular polarization. Measurement results show that the proposed dual circularly polarized MEDA achieves an impedance bandwidth of 84.5%, an axial-ratio bandwidth of 81.8%, and a nearly symmetrical, stable unidirectional radiation pattern with an average gain of 8 dBic over its impedance bandwidth.